Systemic Management of Atopic Dermatitis: New and Emerging Therapies (Actualité en allergologie et en immunologie au Canada, 2022)
Atopic dermatitis, also known as atopic eczema (hereafter referred to as eczema) is the most common chronic inflammatory skin disease worldwide and, together with associated allergies, asthma, allergic rhinitis (with or without nasal polyposis), and eosinophilic esophagitis, atopic disorders represent a growing source of patient morbidity and health care cost globally. The incidence of eczema spans all age groups, but in over 80% of cases it manifests during infancy or early childhood; interestingly, there is now recognition that a significant number of patients suffer from adult-onset, chronic-persistent, and/or late-relapsing disease. Eczema is a complex disease with extreme heterogeneity, including highly variable penetrance, clinical phenotypic presentations (ethnicity, age and temporal factors), and natural history across the lifespan. The term endotype has been introduced to describe potential variance in therapeutic responsiveness and etiology, particularly with respect to genetic and immunologic profiling, as well as environmental triggering. Notably, the range of treatment options available for patients with atopic disorders is changing rapidly, especially for eczema. In this review, we provide a brief overview of targeted systemic therapeutic options for patients with eczema and atopy.